Penguatan Konten Matematika bagi Guru Sekolah Dasar di Kecamatan Takari Kabupaten Kupang - Siprianus Suban Garak; Damianus Dao Samo; Imelda Hendriani Eku Rimo (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
Mathematics material for some elementary school teachers in Takari District, Kupang Regency, NTT is difficult material. So that learning mathematics tends to only train technical skills in counting while understanding and thinking skills are ignored. In general, there are three main problems, namely: 1) many teachers have misconceptions about elementary mathematics material, 2) many teachers have difficulty solving elementary math problems, 3) many teachers are not able to plan mathematics lessons according to the cognitive level of elementary students. So that mathematics is seen as an arithmetic procedure which causes more drill methods to be given to students, there is anxiety in learning mathematics, and learning activities are not innovative. The objectives of this PKM are 1) increasing understanding of elementary mathematics content, 2) developing teacher skills in solving problems and designing elementary mathematics learning, 3) cultivating teacher quality commitment to self-development related to their professional duties. The Strengthening Mathematics Content Activity for Elementary School Teachers was held in the SDI Bokong 1 Hall on June 21-23 2022. The participants in this activity were elementary school teachers in Takari District from 34 elementary schools totaling 50 people. The material presented is numbers and geometry as well as learning. The results obtained by the category of teachers' understanding of elementary mathematics material tended to be good, namely 38% of teachers were in the good category and 62% of the teachers were in the very good category.